Neurodiversity Approaches and Autism (ASD): A Scoping Review - Kushwaha, Ravindra Kumar (CV. Rayyan Dwi Bharata, 2023)
Neurodiversity is a movement that wants to make us think differently about autism. It disagrees with the idea that autism is a disease and instead sees it as a neurological difference: a person who thinks and feels the world in a different way. This article talks about the ideas behind the neurodiversity approaches to autism spectrum disorder (ASD), as well as the conflicts that have come up around these approaches. For example, some people say that neurodiversity approaches only look at society and don't consider the role of individual traits in ASD. This study agrees with other research that both individual and social factors play a role in ASD. This article will be mostly about how to deal with neurodiversity. But even this use of